Good Corporate Governance Mechanism Effect and Green Accounting on Environmental Performance - Inawati, Wahdan Arum; Marwah, Assyifa (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Environmental performance is a company's relationship with the environment in terms of how it uses resources, how organizational processes affect the environment, how products and services affect the environment, how well products are processed, and how well it complies with work environment regulations. Manufacturing sector industrial companies are companies that have a major role as environmental pollution reason. It has been proven that there have been several chemical manufacturing cases of businesses whose surroundings are polluted. The goal of this study is to learn how institutional ownership, managerial ownership, independent commissioner, and green accounting effect environmental performance in from 2018 to 2021, manufacturing companies were listed on IDX. This research uses all data on manufacturers who are consistently recorded on Indonesia Stock Trade and become Appropriate members during 2018-2021 period. Purposive sampling technique used resulted 33 company’s sample. Using panel data regression model, collected data is processed using EViews 12. The findings of this study indicate that independent commissioners have a positive impact on environmental performance. In addition, managerial ownership has no effect on environmental performance, institutional ownership and green accounting have an effect on environmental performance.